Hak Menguasai Negara Atas Mineral dan Batubara Pasca Berlakunya Undang-Undang Minerba - Nalle, Victor Imanuel Williamson (Mahkamah Konstitusi Republik Indonesia, 2012)
Mineral and coal is one of Indonesia’s natural resource potential. Natural resources can bring prosperity for the people of Indonesia. Therefore we need a pro-mining policies of national economic interests. The experience of Indonesia during the New Order show the mining policy in favor of the interests of foreign capital through the mechanism of the work contract that puts the state as the inferior party. State’s right to control the mineral and coal mining policy does not appear in the New Order. Since the enactment of Law Number 4 of 2009, it seemed right to control the state through the licensing system. Besides the role of national capital in the mining sector also raised through divestment mechanism.